A new species of Cavernocypris Hartmann, 1964 (Crustacea: Ostracoda) from caves in South Korea - Smith, Robin James; Kamiya, Takahiro; Choi, Yong-Gun; Lee, Jimin; Chang, Cheon Young (Zootaxa, 2017)
Surveys of caves in South Korea yielded a new species of the ostracod genus Cavernocypris Hartmann, 1964, herein described as Cavernocypris danielopoli Smith & Kamiya n. sp. This is the fifth described species in this widely distributed genus, and can be discriminated from its congeners by the highly triangular shape of the carapace in lateral view, caused by a large dorsal protrusion on the left valve. A second triangular-shaped morphotype was also collected, differing from the first by a lower carapace and less pronounced dorsal protrusion. As it is not clear at present if this represents a separate species or intraspecific variation, it is left in open nomenclature. The lack of a pigmented eye, a highly triangular carapace and no carapace pigmentation suggests that Cavernocypris danielopoli Smith & Kamiya n. sp. is the most adapted species in the genus to a stygobiotic lifestyle. Another Korean species, Cavernocypris coreana (McKenzie, 1972), found in caves and spring discharges, has a reduced number of antennule segments, common for stygobiotic species, but this feature is lacking in the new species. This suggests that within the genus, species have followed different evolutionary pathways to adapt to the subterranean realm.